REPRESENTASI CITRA MUSLIMAH DALAM IKLAN WARDAH COSMETICS “BERGERAK HIDUPKAN HARAPAN” EDISI RAMADHAN 1443 H - Amaniah, Suci; Afyatul Masruroh, Sayyidah (Spektra Komunika : Jurnal Komunikasi & Dakwah, 2024)
Advertising is a promotional medium used by various companies to increase sales of services and goods. Television commercials are believed to be able to influence audiences to purchase products. Moreover, using female figures can increase the appeal of an ad because of their beauty. Many commercials feature female figures showing their curves, such as those featuring women in short, tight clothing. However, unlike Wardah Cosmetics' commercial "Bergerak Hidupkan Harapan" Ramadan 1443 H edition, this ad features women wearing hijab and decently dressed. In addition, Wardah's ads not only showed physical beauty but also the beauty of the heart. This research focuses on the image of Muslim women shown in Wardah Cosmetics' commercial "Bergerak Hidupkan Harapan" Ramadan 1443 H edition. This research concludes that first, there were 15 significant scenes presenting a modern Muslimah, marked by the current Muslim style of clothing and hijab. However, the hijab style used does not fit Islamic law because it does not cover the chest. And the use of Wardah's products on Muslimah actresses leads the audience to keep their faces clean no matter how busy they are and to maintain their appearance at all opportunities. Second, muslimah are depicted as the image of pigura and pinggan. The image of the pigura in this not only shows beauty physically, but also has a beautiful heart. Then the image of pinggan in this commercial shows women in the kitchen not only for cooking but also as a business.